STUDI TENTANG LAYANAN ORIENTASI PADA PESERTA DIDIK KELAS VII DI MTS AL-IRSYAD PONTIANAK - Luthfiah, Qonita; Yuline, Yuline; Wicaksono, Luhur (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to describe the orientation services for seventh grade students in MTS Al-Irsyad Pontianak. The method used is descriptive method in the form of survey studies. The population in this study were all students of class VII MTS Al-Irsyad Pontianak Academic Year 2017/2018. Then the sample is 64 students. Data collection techniques used are indirect communication techniques and documentary study techniques with data collection tools in the form of interviews, questionnaires and documentation. Data analysis techniques are interview data analysis techniques and questionnaire data analysis techniques using percentage formulas. From the data analysis, the researcher found that the counceling guidance teacher had provided orientation services very well to students of class VII MTS Al-Irsyad Pontianak. While the provision of orientation services regarding school discipline has been carried out very well, orientation services regarding the state of the teacher / employee have been carried out quite well, orientation services regarding learning facilities have been carried out very well, orientation services provided by counseling guidance teachers regarding laboratories, school medical room, student computer rooms and so on have been done very well, and orientation services regarding the implementation of extracurricular activities have been carried out very well. Keywords : Orientation Service, Counseling Guidance